CONSTRUCTION OF RECIPROCAL VERBS IN ANGKOLA BATAK LANGUAGE - Harahap, Anna Leli (Journal of English Education and Linguistics, 2024)
This research aims to analyze the syntactic aspects of reciprocal verb construction in the Angkola Batak language (ABl) using binding theory. A qualitative method with a descriptive approach is used in this research. Data were collected through literature study and the author's intuition as a native speaker, then analyzed by agih method and presented informally and formally. The result of the research identifies the formation process of reciprocal verbs in ABl through affixation, affixation+reduplication, and affixation+the word "saling". The characteristics of reciprocal verbs in ABl include intransitive nature, can be followed by the constituent "each other", requires the presence of subject-filling nouns or human complements, and belongs to the category of telic verbs. This study concludes that the binding theory can be applied to analyze the construction of reciprocal verbs in the Angkola Batak language, showing the validity of this theory in the analysis of regional languages. The contribution of this research lies in the documentation and understanding of the grammatical aspects of the Angkola Batak language.